Human placental conditioned medium (from different phase of pregnancy) as a source of colony-stimulating activity for cultures of human and mouse. granulocyte-macrophage colony-forming cells in semisolid agar - Cinátl, J; Lemez, P; Hermanová, E; Chudomel, V; Neuwirtová, R; Neuwirt, J; Zivný, J; Necas, E (Folia biologica, 1981)
We have investigated the effect of conditioned medium derived from cultures of human placental tissue from different phases of pregnancy on in vitro growth of human and mouse granulocyte-macrophage colony forming cells in semisolid agar. We have confirmed that the colony-stimulating activity of human placental conditioned (normal delivery) medium was equivalent to the activity of peripheral blood leucocyte underlayers when medium was added at a 5%-20% concentration to the semisolid agar. Placentas from the 12th amd 10th week of gestation were found not convenient for preparation of medium with high CSA; the activity of media prepared from their cultures was not significantly higher than the autostimulating activity of bone marrow alone. Human placental conditioned medium proved inconvenient for cultures of mouse GM-CFC in semisolid agar containing foetal calf serum.
Keywords: Culture Media; kultivované buňky; faktory stimulující kolonie; těhotenství; Gestational Age; placenta; Granulocytes; Agar; Mice; Placenta; granulocyty; gestační stáří; Cells, Cultured; Macrophages; ženské pohlaví; zvířata; Humans; Colony-Stimulating Factors; Pregnancy; kultivační média; myši; makrofágy; agar; hematopoetické kmenové buňky; Female; Hematopoietic Stem Cells; lidé; Animals